please answer the question fast!!!!
![](https://hi-static.z-dn.net/files/d58/0af55e15c2e388615afe25e247f00a54.jpg)
Answers
Given Equation is x^2 + 1/x^2 = 17/4.
(1)
It can be written as:
⇒ x^2 + 1/x^2 = 9/4 + 2
⇒ x^2 + 1/x^2 - 2 = 9/4
⇒ (x - 1/x)^2 = 9/4
⇒ (x - 1/x) = 3/2 ------- (1)
(2)
It can be written as:
⇒ x^2 + 1/x^2 = 25/4 - 2
⇒ x^2 + 1/x^2 + 2 = 25/4
⇒ (x + 1/x)^2 = 25/4
⇒ x + 1/x = 5/2 ------ (2)
---------------------------------------------------------------------------------------------------------
On cubing (1) on both sides, we get
⇒ (x - 1/x)^3 = (3/2)^3
⇒ x^3 - 1/x^3 - 3(x - 1/x) = 27/8
⇒ x^3 - 1/x^3 - 3(3/2) = 27/8
⇒ x^3 - 1/x^3 - 9/2 = 27/8
⇒ x^3 - 1/x^3 = 27/8 + 9/2
⇒ x^3 - 1/x^3 = 63/8. --------- (3)
On cubing (2) on both sides, we get
⇒ (x + 1/x)^3 = (5/2)^3
⇒ x^3 + 1/x^3 + 3(x + 1/x) = 125/8
⇒ x^3 + 1/x^3 + 3(5/2) = 125/8
⇒ x^3 + 1/x^3 + 15/2 = 125/8
⇒ x^3 + 1/x^3 = 125/8 - 15/2
⇒ x^3 + 1/x^3 = 65/8.
Hope it helps!